Valuation Analysis of Mini Hydro Power Plant Using Value at Risk Method - Purnomo, Satria Mulia; Moeis, Armand Omar (Indonesian Journal of Multidisciplinary Science, 2025)
The Paris agreement made Indonesia committed to the renewable energy transition. This commitment encourages Indonesia and PLN to make RUPTL which increases the potential for hydropower in Indonesia. This increased potential has attracted investors to invest in the MHP business. However, the MHP business still has risks that make costs fluctuate, disrupting prospects and causing doubts in investment. To overcome this problem, the authors created a financial projection model using a discounted cash flow model with a risk approach using the value at risk monte carlo method so that it can measure MHP valuations more accurately and can provide investment feasibility considerations.  This study examines the financial viability of Mini Hydro Power Plant (PLTM) investments in Indonesia, where renewable energy development faces risks from fluctuating costs and uncertain returns. The research aims to evaluate PLTM project risks using the Value at Risk (VaR) method combined with Monte Carlo simulation, focusing on three key variables: loss factor (7%), operational costs, and water retribution fees. Financial data from a West Sumatran PLTM company was analyzed through discounted cash flow (DCF) modeling with a 3% discount rate, supplemented by 10,000-iteration Monte Carlo simulations at 95% confidence levels. Results indicate positive NPV values under normal conditions (Rp161.6 billion), demonstrating investment feasibility, while sensitivity analysis shows potential 8-22% valuation improvements with reduced loss factors. The study provides investors with a risk-assessment framework and suggests infrastructure optimization could enhance PLTM profitability.